Special papersPregnancy after myocardial infarction and coronary artery bypass grafting – is it safe? - Janion-Sadowska, Agnieszka; Sadowski, Marcin; Zandecki, Łukasz; Kurzawski, Jacek; Polewczyk, Anna; Janion, Marianna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Pregnancy after myocardial infarction (MI) and coronary artery bypass grafting (CABG), although still rare, is slowly becoming a challenge in everyday clinical practice. In recent decades MI has been observed to occur more frequently in young women. Concurrently an increasing number of women decide to become pregnant at more advanced age. Although pregnancy after MI and CABG may be possible and safe, a multidisciplinary approach involving careful evaluation by the cardiac and obstetric team in each individual is mandatory. Two cases of pregnant women with a history of MI treated with CABG are presented and their management is discussed.